Inguinal lymphadenopathy as the initial presentation of sarcoidosis - George, Jim (Baylor Health Care System, 2013)
Sarcoidosis is a multisystem disease of unknown etiology characterized by granuloma formation. Despite pulmonary involvement in most patients, sarcoidosis can have a varied presentation. Lymph node involvement is rarely found in isolation. Even rarer are cases of sarcoidosis presenting with peripheral edema. We describe a case of sarcoidosis presenting with isolated unilateral peripheral edema.